2020
DOI: 10.1177/0038040720910128
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Schools in Changing Places: Examining School Enrollment in Gentrifying Neighborhoods

Abstract: School choice expansion in recent decades has weakened the strong link between neighborhoods and schools created under a strict residence-based school assignment system, decoupling residential and school enrollment decisions for some families. Recent work suggests that the neighborhood-school link is weakening the most in neighborhoods experiencing gentrification. Using a novel combination of individual, school, and neighborhood data that link children to both assigned and enrolled schools, this study examines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 63 publications
2
26
0
Order By: Relevance
“…This implies that school choice policies, which have been firmly in place in the Dutch context for many decades, take away some of the anxieties and perceived necessity of moving away from socially and ethnically mixed areas. This is consistent with the findings of (Pearman & Swain, 2017), who found that school choice may support gentrification and that school choice policies are partly a response to the ongoing gentrification of urban neighbourhoods (Candipan, 2020). In fact freedom of school choice may be a sine qua non of substantial presence of middle-class families in the city (family gentrification) (Boterman, 2019;Karsten, 2007).…”
Section: Conclusion and Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This implies that school choice policies, which have been firmly in place in the Dutch context for many decades, take away some of the anxieties and perceived necessity of moving away from socially and ethnically mixed areas. This is consistent with the findings of (Pearman & Swain, 2017), who found that school choice may support gentrification and that school choice policies are partly a response to the ongoing gentrification of urban neighbourhoods (Candipan, 2020). In fact freedom of school choice may be a sine qua non of substantial presence of middle-class families in the city (family gentrification) (Boterman, 2019;Karsten, 2007).…”
Section: Conclusion and Discussionsupporting
confidence: 79%
“…Residential practices of middle-class parents are strongly driven by the quest for good schooling for their children (Bridge & Wilson, 2014;Holme, 2002). Despite policy changes expanding parental choice (Ball, 2003;Le Grand, 2007), access to high-quality (public) education in most studied contexts is still largely determined by residential proximity and thus contingent on the conditions of the housing market (Burgess et al, 2011;Candipan, 2020;Hamnett et al, 2013;Holme, 2002). In socially and ethnically diverse urban neighbourhoods in particular, (white) middle-class parents play "games of proximity and distance" (Andreotti et al, 2013) in which "black schools" (Boterman, 2013;Saporito & Lareau, 1999), "rough schools" (Benson et al, 2015), and "poor quality" schools are avoided and schools are carefully selected in search of the "right mix" (Billingham & Hunt, 2016;Butler & Hamnett, 2012;Raveaud & Van Zanten, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Surveys and exper i ments eval u at ing school search pro cesses reveal that White par ents often start with school racial com po si tion as a short hand heu ris tic device (Saporito and Lareau 1999;Schneider and Buckley 2003) before weighing other edu ca tional char ac ter is tics. Perhaps this search behav ior explains why White children dis pro por tion ately enroll in choice schools when their neigh bor hoods (and assigned local schools) have siz able Black and His panic pop u la tions (Bischoff andTach 2018, 2020;Candipan 2019Candipan , 2020Saporito 2003;Saporito and Sohoni 2007). The uniquely racialized school selec tion behav ior of White fam i lies has thus raised 5 Segregated Neighborhoods, Segregated Schools con cerns that char ter schools facil i tate White flight from TPSs (Bifulco et al 2009;Frankenberg et al 2011;Renzulli and Evans 2005).…”
Section: Charter Expansion and School Segregationmentioning
confidence: 99%
“…However, today about 45% of children in metropolitan areas attend a nonassigned K–12 school (Candipan 2020). This shift reflects two trends fueled by the school reform movement, which embraced market-based principles as an antidote to educational inequities.…”
Section: Parental Depression and School Selectionmentioning
confidence: 99%
“…Predicated on market principles, such as choice, information, and competition, reforms softened long-standing school enrollment residency requirements, facilitated the proliferation of school quality data, and fueled the expansion of nontraditional public school options, including charter and magnet schools (Archbald 2004;Berends, Waddington, and Schoenig 2019;Orfield and Frankenberg 2013). About 45% of children in metropolitan areas now opt out of their residentially assigned public school (Candipan 2020). Yet the school sorting literature has not thoroughly examined whether parents' socioemotional health shapes this complex and high-stakes decision-making process.…”
mentioning
confidence: 99%